Terminação de novilhas em capim Tifton 85 suplementadas com diferentes fontes energéticas - Cardoso, Gilmar dos Santos (2020)
The objective of the present study was to investigate different energy supplements in the termination of heifers discarded in pasture of Tifton 85 grass. The experimental area used corresponded to 4.5 hectares of Tifton 85 grass (Cynodon ssp.), Divided into 15 paddocks of 0, 3 ha each, in which the test animals were handled. The experimental period was from December 24, 2016 to April 14, 2017, totaling 112 days, divided into four periods of 28 days. Thirty culling heifers were used, originating from the continuous alternating crossing between the Charolais and Nellore breeds, with an average age of 26 months, with an initial average body weight of 274.5 kg. Each treatment consisted of five area repetitions (paddocks), with two experimental units (animals), totaling 10 animals per treatment. The treatments were comprised of the different energy sources of supplementation, these being: TM = Corn grain supplementation + Tifton 85 pasture; TA = White Oat supplementation + Tifton 85 pasture; TC = Barley supplementation + Tifton 85 pasture, at the level of 1.0% of body weight based on dry matter (DM). The grazing method adopted was the continuous one with variable capacity, using the “put-and-take” technique. For animal performance evaluation, the animals were weighed at the beginning and at the end of each experimental period, which was 28 days, after a 12-hour fasting of liquids and solids. Animal behavior observations were made in all paddocks for each treatment, in which behavioral assessments were carried out for 24 hours uninterrupted. Throughout the daytime observation period, at different grazing intervals, the time that each heifer required to travel ten feeding stations and the number of steps between these stations was recorded. The experimental design was completely randomized with five replications per area, in a 3 x 4 factorial (three treatments x four periods). The average daily weight gain of heifers showed only numerical differences (P> 0.05) between energy sources in supplementation. For all food treatments, there was a linear increase in the number of steps between seasons (P <0.05).